Studi Komparasi Manajemen Pembelajaran Bahasa Arab Di Kelas XI MAN Sabdodadi Bantul Dan Kelas XI MA As Sakinah Hidayatullah Sleman - Rizal Effendi Putra (Taqdir, 2021)
This study aims to determine the differences in learning management implemented in Arabic learning by class XI teachers at Madrasah Aliyah Negeri Sabdodadi Bantul and class XI at Madrasah Aliyah As Sakinah Hidayatullah Sleman Yogyakarta as well as the factors that support and hinder the realization of effective learning. With this research, it is hoped that it can provide input in improving the learning process for all parties, especially Madrasah Aliyah Negeri Sabdodadi Bantul and Madrasah Aliyah As Sakinah Hidayatullah Sleman Yogyakarta. The results of the study indicate: Arabic learning management can be seen from the management functions carried out by the teacher, namely: lesson planning, research results show lesson planning such as syllabus, lesson plan (RPP), daily program, semester program and annual program. on the academic calendar that has been agreed upon by the regional office (Kanwil). Meanwhile, MA As Sakinah Hidayatullah uses a curriculum that has been prepared by the madrasah, namely the kurikulum diniyah and the Arabic language learning syllabus is also compiled by the madrasah. As for each planning identity, it is only written for class XI A MA and XI B MA. Because in MA As Sakinah, especially in class XI, there are no majors.